Combining mGRASP and Optogenetics Enables High-Resolution Functional Mapping of Descending Cortical Projections - Song, Jun Ho; Lucaci, Diana; Calangiu, Ioana; Brown, Matthew T. C.; Park, Jin Sung; Kim, Jinhyun; Brickley, Stephen G.; Chadderton, Paul (CELL PRESS, 2018)
We have applied optogenetics and mGRASP, a light microscopy technique that labels synaptic contacts, to map the number and strength of defined corticocollicular (CC) connections. Using mGRASP, we show that CC projections form small, medium, and large synapses, and both the number and the distribution of synapse size vary among the IC regions. Using optogenetics, we show that low-frequency stimulation of CC axons expressing channelrhodopsin produces prolonged elevations of the CC miniature EPSC (mEPSC) rate. Functional analysis of CC mEPSCs reveals small-, medium-, and large-amplitude events that mirror the synaptic distributions observed with mGRASP. Our results reveal that descending ipsilateral projections dominate CC feedback via an increased number of large synaptic contacts, especially onto the soma of IC neurons. This study highlights the feasibility of combining microscopy (i.e., mGRASP) and optogenetics to reveal synaptic weighting of defined projections at the level of single neurons, enabling functional connectomic mapping in diverse neural circuits.
Keywords: INFERIOR COLLICULUS; AUDITORY-CORTEX; SYNAPTIC CONNECTIVITY; SYNAPSES; LOCALIZATION; NUMBER; AREA